CONSTRUCTIVE GEOMETRY IN IMPLEMENTATIONS OF MODERN 3D GRAPHICS - Ivan G. Lenchuk; Oleksandr O. Mosiiuk (Інформаційні технології і засоби навчання)
3D graphics are one of the crucial development trends of modern digital technologies. Engineering and manufacturing, architecture, design, cinematography, education, and the game industry are an incomplete list of industries where it is actively used. Specialists in 3D graphics are in high demand in the labor market. Their proper training presupposes high-quality knowledge of geometrical sciences, in particular – constructive geometry. Note that constructive geometry is an integral part of modern school mathematics education. That is why, even in the conditions of the school, the teacher should skillfully apply the demonstration capabilities of three-dimensional graphics. It will also encourage students of a comprehensive school to apply knowledge of constructive geometry in practice in the area of 3D modeling. This approach will make it possible to demonstrate the importance and interconnectedness of knowledge in geometry and computer science. Therefore, the article reveals the importance of interdisciplinary connections between the specified disciplines in the context of research, demonstration, and application aspects. In particular, the nuances of using the GeoGebra dynamic geometry complex for conducting computational experiments and creating spatial models based on tasks from a school spatial geometry course are described. After all, modern capabilities of software tools make it possible to demonstrate in real time all the transformations that took place during drawing modeling on the picture plane. The importance of the applied value of constructive geometry for 3D modeling reveals based on examples of solid and polygonal modeling of virtual spatial objects. In particular, the steps of creating a solid model of a pyramid, which is formed by cutting it off with a plane from a regular quadrangular pyramid, are illustrated by the basis of calculations and constructions, which are performed using techniques of constructive geometry. All stages are described and done using the TinkerCAD online modeling service tools. An example of using the Blender program for creating polygonal 3D models is also provided. In particular, the significant aspects of the part modeling process are presented in the example of a task from a drawing textbook. The importance of planimetric constructions in the process of performing high-precision polygonal modeling is also emphasized. The article contains many figures that illustrate the essential stages of modeling. The materials presented can be used to prepare lessons in either mathematics or computer science and can be used to conduct integrated classes that draw on both subjects. Possible prospects for further research on this topic are also presented.